Biomimetic Sulfide Oxidation by the Means of Immobilized Fe(III)-5, 10, 15, 20-tetrakis(pentafluorophenyl)porphin under Mild Experimental Conditions. (3rd October 2013) - Zucca, Paolo; Cocco, Gianmarco; Pintus, Manuela; Rescigno, Antonio; Sanjust, Enrico
Abstract : This paper describes the oxidation of inorganic sulfide to sulfate, minimizing the formation of elemental sulfur. The described catalytic reaction uses dilute hydrogen peroxide at nearly neutral pH values in the presence of a bioinspired, heterogenized, and commercial ferriporphin. A substantial increase of the percentage of sulfide converted to sulfate is obtained in comparison with the yields obtained when working with hydrogen peroxide alone. The biomimetic catalyst also proved to be a much more efficient catalyst than horseradish peroxidase. Accordingly, it could be suitable for large-scale applications. Further studies are in progress to drive sulfate yields up to nearly quantitative.